Hydrogel and its textile composite materials in the heavy metal removal research progress - Kiral, Gizem; Cacciola, Andreas (Journal of Functional Materials and Applied Engineering, 2024)
With the rapid development of industrialization, global water resource shortages and heavy metal pollution problems occur frequently, seriously threatening ecological security and human health. This article expounds on the research status of heavy metal removal technology, analyzes in detail the characteristics and limitations of carbon-based materials, metal-organic frameworks, and biomass adsorbents. By focusing on hydrogel materials, it explains their three-dimensional network structure and physical/chemical cross-linking mechanisms, and summarizes the application progress of natural, synthetic, and composite hydrogels in heavy metal adsorption. Combined with the multidimensional structure and mechanical properties of textile materials, it discusses the functional modification strategies and adsorption efficiency of one-dimensional to three-dimensional textile materials. On this basis, it proposes the design of hydrogel textile composite materials, optimization of mechanical strength, improvement of selective adsorption, and enhancement of green preparation processes, in order to promote their large-scale application in heavy metal pollution control and provide innovative solutions for building a safe and sustainable water resource system.